Peran Softskill Dan Pengembangan Karyawan Terhadap Kualitas Kerja - Lusi Nur Fajriani; Faizal Mulia Z; Nor Norisanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the influence between soft skills and employee development variables on work quality. This study uses quantitative methods. The population in this study are employees of PT. Bakti Wira Karsa Sakti (Save on Department Stores and Wholesalers) and the sample used is 100 respondents. The data analysis technique used is multiple linear regression analysis and the sample technique used is probability sampling. The results of this study indicate that simultaneously and partially the soft skills and employee development variables have a positive and significant influence. The results of the f test are known from the Fcount 59.275 > 3.08, indicating that the Fcount value is greater than Ftable and from the correlation results in this study, it has a strong and high value of 0.742. Meanwhile, from the results of the t-test value, namely Tcount 7.058 > 1.983, it shows that Tcount is greater than Ttable, so it can be concluded that the soft skills and employee development variables have an influence on work quality. Keywords: Softskill, Employee Development, Work Quality